O impacto da aplicabilidade de tecnologia de placa fotovoltaica voltada para residência familiar usando prospecção tecnológica - Guimarães, Daiane Costa (2016)
The growing demand for energy, the rising cost of fossil fuels and concern for the environment led to an improvement in the power generation sector from renewable resources. The sun, by its omnipresence in virtually all living spaces on the planet, is an energy source with great prospects. In this context, it is crucial in the search for alternative sources of renewable energy and clean, like solar. The choice of a photovoltaic solar system at home is part of a strategic policy of sustainable development, the main objectives the option of a viable solution from an economic point of view and from a social point of view, with very positive impact on the people are aware of the need to opt increasingly for renewable energy. Thus, this thesis analyzes the impact of the application of photovoltaic panels focused technologies for family residence using the technological prospecting tools. The methodology was based ondata in Espacenet database, using the key - words in the title and abstract: Plate and photovoltaic and house, and found 79 patents applications, but were only released for consultation 75. It was noted the existence of applicants from the year 2001, and the years that had higher numbers of applicants were 2012 and 2014. Despite the cost of the technology of photovoltaics still be high, it was possible to observe the results that there is an increase in patent applications. Of the total number of patent documents found in the study, 86% was applied in China, which has introduced several incentives in relation to renewable energy and runs programs that stimulate technological innovation, especially in areas considered as priorities, such as solar energy. Also worth mentioning that the main inventors and applicatorshave Chinese nationality, a fact that confirms the dominance of the Asian country as the main applicant. Moreover, the International Patent Classification was the most abundant E04D13 / 18 (47%), which involves supporting structures of photovoltaic modules adapted especially for roof structures. Analyzing the profile of applicators, it was found that 55% of patent applications has as holders companies, while individual inventors have a representation of 41% of the technologies developed, and universities account for only 4% of the developments. The research showed, finally, regarding the estimated impact that 72% of patents are directed to use in family residence, specifically on roofs, solar shingles among others, that companies and / or research institutions can develop better strategies and planning the desired future of their products in order to meet certain market segments.